The geochemistry of minor elements in Pernambuco soils. III. Copper in the Zona Litoral-Mata - Horowitz, Arão; Dantas, Humberto da Silveira (Pesquisa Agropecuaria Brasileira, 2014)
Eleven typical soil profiles of the region known as the "Zona Litoral-Mata" in the State of Pernambuco were studied. These profiles represent the major soil types of the coastal region, the state most important agricultural area. The total and soluble copper content in these soils was determined by atomic absorption spectrometry. The extractants used for determining soluble copper were selected from those reported in the literature and are considered to be the most suitable for making plausible deductions as to the geochemistry and availability of this element. The total copper content in some of these soils is surprisingly high, considering that most of these soils are reported to be derived from acidic rocks. In general, the soils studied were found to be quite normal in total copper content, ranging from 2.2 ppm to 79.4 ppm in the surface horizon. The data available strongly suggests trat this metal is present in a moderately stable form in the lattice of the ferromagnesian minerals (mostly biotite an homblende). In richer soils it is also absorbed by iron and manganese concretions, principally by the last. In these soils copper shows a tendency to concentrate in the surface horizon, where it appears to be bound to the soil organic matter and to the clay minerals. There is also certain tendency for the copper to accumulate in the iluvial horizon. In order to tentatively predict the copper deficient soils, the element was determined by extraction with 0.1M HCI, and 0.5M acetic acid and 0.05M EDTA. The results obtained by all methods, including total copper, agree reasonably well. Neverthless, the last extractant was considered the most satisfactory, although the available data is not sufficient to support a final conclusion. Greenhouse experiments are being planned to provide more pertinent data. Only four soils types from Nazaré da Mata, Paudalho, Moreno and Ribeirão counties have a 0.05M EDTA extractable copper content below the level considered to be deficient (about 0.6 ppm) for pastures and crops growing in these soils. Perhaps it is justifiable to expect symptoms of copper deficiency on crop and pastures from these soils. This also holds true for animals fed only on crops grown on these soils. As for the remaining soils, four seem to contain an adequate supply of copper; they are from Timbaúba, Aliança, Cabo and Barreiro counties. The last three soils from Goiana, Água Preta and Quipapá counties will probably show copper deficiency within a comparatively short time when submitted to intensive culture.